Analisis Kebijakan Smart City Pada Among Tani untuk Menumbuhkan Partisipasi Masyarakat dalam Rangka Mewujudkan Good Governance - Wole, Bewa Dangu; Sasmito, Cahyo; Purwaningsih, Anisa (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2021)
To realize good governance is inseparable from community participation, the government initiated a concept of smart city implementation. Smart city is a form of structuring and managing the City using technology-based resources. Batu City Government, the term smart city was changed to Batu Among Tani Teknologi. The purpose of the research is to analyze smart city policies in Among Tani to increase community participation in order to realize good governance in batu city government, to know the supporting factors and inhibitions and to know the smart city policy analysis model. The method in this research is qualitative research approach of literature study using secondary data derived from books, journals, and other scientific critical studies coming from institutions according to the focus of research topics. The results of the research obtained are the application among farmers in Batu city community participation is increasing because farmers can market agricultural products and survive the practice of middlemen, consult and report complaints on the application Among Farmers and also farmers empowered through farmer groups. Not only farmers who use the application, the general public as buyers have also used Among Tani. The supporting factor of smart city policy in Among Tani is the organization of farmers who are empowered in farmer groups so that the needs of the people of Batu city the results of agriculture are fulfilled. The inhibition factor is the lack of evenly distributed socialization of the government so that there are still many people who do not understand what smart city is and the presence of farmers lose the motivation of farming that results in agricultural land being switched because of the lack of protection from the government.